Microscopic Theory for Spontaneous Fission - Sadhukhan, Jhilam (Frontiers in Physics, 2020)
Nuclear fission is a fascinating field of research that involves large-amplitude collective dynamics of a microscopic many-body system. Specifically, the process of spontaneous-fission decay can only be explained within the quantum tunneling phenomenon. The present review discusses recent developments in the filed of theoretical understanding of spontaneous fission. These are primarily based on the nuclear energy density functional theory. The main motivation behind all these studies is to predict the spontaneous-fission observables like fission-lifetime and fragment properties starting from the underlying nucleon-nucleon interactions.